(untitled) (Research, Society and Development, 2021)
Objective: to characterize the scientific evidence on the health promotion strategies of nursing workers during the Covid-19 pandemic. Methodology: this is an integrative review study that aims to characterize the evidence available in the literature on strategies to contain the health of nursing workers during the Covid-19 pandemic. Results: six (n=6) studies were selected, among which five (n=5) were produced in Brazil and published in national journals, only one article found was of international origin, regarding the levels of evidence, all articles included in this review, they were classified as evidence level V, as they have the descriptive approach as a method. Conclusion: the studies included in this review come to characterize the difficulties encountered by nurses in the pandemic scenario, as well as the strategies adopted by organizations (such as unions), hospital institutions, or even the sensitivity of other professionals in the multidisciplinary team, for the physical and psychological care of the nursing team. It is hoped that the results of this study will contribute to the reflection, reproduction and encouragement of these strategies and new studies that address the culture of worker’s health.